Aplicação de um sistema balanceado de métricas como instrumento de gestão estratégica do capital intelectual: um estudo de caso - Morandi, Julio Carlos (2004)
The business world has been changing in a fast and continuous way and the present moment leads the economy to a transition from Industrial Society to a Society based on Knowledge. In this context, there comes to appear new models of organization management where the focus comes to be the searching of unreachable actives in order to add more value to products and services offered by enterprises. Because of the characteristics of the Urban Passengers Transportation business model where the State happens to be the main actor, both in the offer of services regulamentation as in the prices (taxes) fixing and with the objective to contribute to the discussion about the participation of the Intellectual Capital in the enterprises market value of this segment, the present work presents the application of a Balanced Measurement System, based on Balanced Scorecard model, by Kaplan & Norton, created to measure the performance in financial and non-financial dimensions, in order to evaluate the evolution not only of the tangible assets, but specially the intangible ones. Using a case study, this model was applied in an urban passenger s transportation enterprise, in order to evaluate the Intellectual Capital value growth for a three years period, which was not demonstrated in its traditional Financial Balances. The model appeared to fit the proposes, leading to a conclusion that the intangible assets in the enterprises where the survey was conducted are strategic factors that takes it to the growth of his market value, even there are no investments in tangible assets